Efektivitas Implementasi Teaching at the Right Level (TaRL) Dalam Meningkatkan Hasil Belajar Passing Bawah Bola Voli Pada Siswa Kelas IV SDN Bulusari 1 - Agas Corry Fernando; Wasis Himawanto; Dwi Sulistyo Nugroho (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study discusses the effectiveness of the implementation of the Teaching at the Right Level (TaRL) approach as an effort to improve the learning outcomes of volleyball underhand passing in grade IV students of SDN Bulusari 1. The design of this study uses Classroom Action Research (CAR). CAR is a research approach designed to improve learning practices in the classroom with the aim of providing a more comprehensive picture of the situations and practices that occur in the classroom, as well as to improve the overall quality of learning. Data collection in this study was carried out through two cycles, with a total of six meetings. The location of the study was at SDN Bulusari 1, Tarokan District, Kediri Regency, East Java. The sampling used was cluster random sampling where the selection process was carried out randomly. The sample used was grade IV (four) students with a total of 28 students. Analysis of research data on the volleyball underhand passing learning process used the Teaching at the Right Level (TaRL) approach. Based on the results of the study, it can be concluded that learning underhand passing will show an increase in percentage from cycle I to cycle II, namely from 73.9% to 86.4%. In addition, the percentage of student completion in cycle I reached 57.14%, then increased significantly to 92.85% in cycle II.